The impact of AI Chatbots on customer satisfaction with special reference to Fintech companies - Wickrama Arachchighe, Nuwan (2025)
The rapid advancement of Artificial Intelligence (AI) has transformed custom-er service in the digital space, particularly through the integration of AI chat-bots within Fintech companies. This study investigates the impact of AI chat-bots on customer satisfaction, focusing on key factors such as perceived use-fulness, perceived ease of use, system quality, information quality, and service quality. Drawing on established theoretical frameworks - including the Tech-nology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), Expectation-Confirmation Theory (ECT), and SERV-QUAL - the research adopts a quantitative approach, surveying a sample of Fintech users with prior chatbot interaction experience.